Dielektrická rezonátorová anténa - Štarha, Michal (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2010)
Tato práce pojednává o využití dielektrických rezonátorů jako antén. Jsou zde probrány možnosti napájení těchto antén, jako je napájení sondou, mikropáskovým vedením, štěrbinou, či koplanárním vedením. Poté je zde ukázka návrhu jednoduché pravoúhlé dielektrické rezonátorové antény a její simulace v programu CST Microwave Studio. Navržená anténa je vyrobena a změřena.

This project deals with using of dielectric resonators as antennas. There are discussed possibilities feed of these antennas, as feed probe, feed of microstrip line, aperture coupling, or coplanar waveguide. Then there is a simple example design dielectric resonator antenna and its modeling in CST Microwave Studio. The designed antenna is fabricated and measured.
Dielectric resonator antenna
Keywords: Dielektrický rezonátor; dielektrická rezonátorová anténa; CST Microwave Studio.; Dielectric resonator; dielectric resonator antenna; CST Microwave Studio